Prerequisite of Insulin and Intravenous Fluid in the Treatment of Diabetic Ketoacidosis to Overwhelmed the Catastrophe - Tariq Tahir Butt, Sobia Muhammad Ilyas, Syed Mir Usman Shah, Muhammad Azam, Amanullah Khokhar, Ayesha Shafique, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Ketoacidosis (DKA) is relatively common among the states of acute metabolic decompensation of diabetes. It usually transpires in patients with diabetes mellitus who have some type of infection and have poor compliance of insulin. Treatment entailed of correcting hyperglycaemia, dehydration, acidosis, electrolyte imbalance and antibiotic therapy in patients with any type of infection or treating another reason, if any. The aim of this study is to determine the requirement of insulin and intravenous fluid for the treatment of diabetic ketoacidosis to overcome the catastrophe Study Design: It was a cross-sectional study, held in the Medicine of Sialkot Medical College, Sialkot for six-months duration from July 2021 to December 2021. Methods: Sixty adult patients with DKA who met the exclusion and inclusion criteria who need the total volume of intravenous fluid (saline) required to manage diabetic ketoacidosis. Results: The total numbers of selected patients were 60. Diabetic ketoacidosis was communal in patients with formerly detected diabetes (71.4%), and its frequency was higher in the poor and the rural population, no significant gender differences were found. Vomiting (53.3%), Nausea (36.7%), infection (38.3%) and abdominal pain (30%) were common, with polyuria (25%) and polydipsia (18.3%). The main causes were infection (38.3%) and failure to administer insulin (51.7%). In most cases, status of glycaemia was poor. Many of the cases had mild (43.3%) to moderate (56.7%) acidosis, and electrolyte disturbances were less frequent. Leucocytosis (90%) was consistently present even in the absence of any infection. The result (91.7% survival) is comparable to that of developing countries. For the treatment of CKD, 35% of patients with increased diuresis required 11 liters of fluid. 23.3% of patients required 91-100 insulin units, and maximum patients (31.7%) needed forty-eight hours to correct their acidosis. Conclusion: Diagnosing diabetic ketoacidosis is not tough if noticed in time and can be treated successfully. In order to prevent mortality; adequate fluid replacement is mandatory. Keywords: Diabetic ketoacidosis, diabetes, intravenous fluids and insulin.